Native History and Nation Building on Personal Online Platform: Implications in Hong Kong Context - Simin Li (Social Sciences, 2019)
Nationalism in the era of social media is more complex and presents new opportunities and challenges in different levels and contexts. Therefore, the paper hopes to contribute to understanding the roles of social media in identity presentation and formation in a transition society. Writing on Facebook is a civil practice. Thus, it chooses a typical and clear-cut Facebook fan page “Hong Kong National History„ run by a nationalist and followed by over 5700 fans as a case study. Posts of the fan page are collected from 1 April to 31 December in 2017, and it analyzes the contents and forms of posts with content analysis. Then, the self-made digital publication “Hong Kong People’s History of the Thousand Years„ attached to the fan page is analyzed with narrative analysis. Through the personal systematic discourses, this paper presents a special mode of user-generated content online and a civic Hong Kong story.